Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “Crangonyx floridanus complex” - Cannizzaro, Andrew G.; Sawicki, Thomas R. (Zootaxa, 2019)
Crangonyx ephemerus n. sp. and Crangonyx pseudoephemerus n. sp. are described from the headwaters of the St. Marks River in Leon County, Florida, based on detailed morphological and molecular comparisons with the closely related species Crangonyx floridanus Bousfield, 1963. The morphological and molecular data, including three species delimitation models, lend support to the hypothesis that the taxon C. floridanus sensu lato represents a species complex. Diagnostic morphological characteristics are highlighted and discussed within this group to assist in future morphological analyses.